Recovery of rat growth and lipid profiles in adult rats subjected to fetal protein malnutrition with a fructose-rich diet - Cambri, Lucieli T. [UNESP]; Ghezzi, Ana C. [UNESP]; Ribeiro, Carla [UNESP]; Dalia, Rodrigo A. [UNESP]; Rostom de Mello, Maria A. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2010)
There is evidence suggesting an association between fructose consumption and the development of metabolic syndrome. In turn, protein malnutrition in utero is proposed to "program" the fetal tissues, making them more susceptible to nutritional associated disorders. To test this hypothesis, the present study was designed to analyze body growth and metabolic aspects of rats subjected to fetal protein malnutrition and subsequently fed a fructose-rich diet. Wistar rats were distributed into 4 groups: balanced (B) diet B diet offered the entire experimental period; balanced diet/fructose B diet until birth and fructose-rich diet (F-60% fructose) until adulthood; low-protein (L) diet/balanced L diet until birth and B diet until adulthood; low-protein diet/fructose (F) L diet until birth and F diet until adulthood. After nutritional recovery, there was a restoration of serum glucose, total protein, and albumin concentrations, which were reduced by fetal malnutrition, and a restoration of the liver glycogen and lipids contents, which were increased by fetal malnutrition. This restoration was independent of the diet adopted after birth. It was verified that the high fructose diet arrested body growth of the rats independently of the nutritional state during fetal life and was associated with weight reduction and decrease of the adipose in some regions of the body (P < .05). Moreover, the serum concentrations of triglycerides and total cholesterol, which are indicators of metabolic syndrome, rose in the rats that ingested the fructose-rich diet (P < .05). In summary, high consumption of fructose impairs body growth and alters the circulating lipids independently of the protein nutrition in utero. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Rat; Low protein; Nutritional recovery; Development; Fructose; Syndrome metabolic